Edukasi penggunaan sediaan tabir surya sebagai upaya pencegah penuaan dini dan kanker kulit di SMAIT Anak Sholeh Mataram - Windah Anugrah Subaidah; Wahida Hajrin; Yohanes Juliantoni (Universitas Mataram, 2023)
Prolonged sun exposures can have negative impacts to skin such as premature aging and skin cancer. These impacts can be minimized by using sunscreen. Unfortunately, majority of Lombok islanders, especially students, still not aware on sunscreen benefits and applications. Therefore, community service is conducted to educate on the danger of prolonged sun exposures on skin and on how to apply sunscreen to prevent skin aging and skin cancer. The method consists of preparation stage, pre-test, education, and evaluation. The community service on SMAIT Anak Sholeh Mataram is considered to be positive by the involved party. This activity has been an early education for the students about how to prevent premature aging and skin cancer. Furthermore, the test result shows there is a positive increase on the training participants’ knowledge.